Reforming Education Since the Year 2000: The Case of Russia - Nikandrov, Nikolay Dmitrievich (International Dialogues on Education Journal, 2014)
This paper analyzes the reformation of Russian education since the disintegration of the Soviet Union, with an emphasis on what happened since the year 2000. It is shown how the 1990s innovative changes were burdened with challenges and problems. The present-day trends and plans include introducing of education standards, making preschool education available to all families, raising school and university teachers’ salaries, keeping and widening access to quality education while restructuring (sometimes closing) ineffective institutions, encouraging gifted students, and improving teacher training and school facilities. All this will be possible if financing education is kept stable and gradually increased and if evolutionary change is accepted as general practice with no more revolutionary upheavals.